Correlates of substance use and dependence among internally displaced persons in Maiduguri, Nigeria - Aluh, D.O.; Okoro, R.N.; Aigbogun, Osaro (2023)
Background: Internally displaced persons (IDPs) are frequently subjected to traumatic events, making them vulnerable to using substances. This study explores predictors and types of substances used by IDPs, prevalence of substance dependence, and reasons for substance use. Methods: Cross-sectional survey data were obtained from 520 IDPs living in camps located in Borno State, Nigeria. The Drug Use Disorders Identification Test (DUDIT) was adapted and administered to the participants. IBM SPSS was used to conduct univariate and multivariate linear regression analyses. Results: More than half (66.2%, n = 344) of the survey participants used at least one substance while a third of them (31.2%, n = 162) used more than one substance. About one in ten respondents met the instrument cut-off for dependence. The most popular substance used was Kolanut (46.5%, n = 242). Popular reasons for substance use were availability of substance, influence from others, and having a disease condition. Education, marital status, employment, and number of substances used were significantly associated with substance dependence. Conclusions: A high prevalence of substance use was found among the IDPs. The study highlights the need for intervention in the substance use problem affecting this vulnerable population.